A week at the shore - Delinsky, Barbara (St. Martin's Press, 2020)
"One phone call is all it takes to lure Mallory Aldiss back to her family's Rhode Island beach home. It's been twenty years since she's been gone - running from the scandal that destroyed her parents' marriage, drove her and her two sisters apart, and crushed her relationship with the love of her life, Jack Sabathian.Twenty years during which she lived in New York, building her career as a photographer and raising her now teenage daughter Joy. But that phone call makes it clear that something has brought the past forward again - something involving Mallory's father. Compelled by concern for her family and by Joy's wish to visit her mother's childhood home, Mallory returns to Bay Bluff, where conflicting loyalties will be faced and painful truths revealed. In just seven watershed days at the Rhode Island shore, she will test the bonds of friendship and family - and discover the role that love plays in defining their lives."--Provided by publisher.